PENGARUH PERGANTIAN MANAJEMEN, OPINI AUDIT DAN UKURAN KAP TERHADAP PERGANTIAN AUDITOR - Erlangga Trixie Pratama (2022)
This research was conducted to find empirical evidence regarding the effect of management change, audit opinion and KAP size. Determination of the sample in this study used a purposive sampling method so that there were 330 observations consisting of 66 private service companies listed on the Indonesia Stock Exchange in 2017-2021. This study uses logistic regression analysis with the SPSS 26 program. The test results state that change of management, audit opinion has no effect on auditor switching while KAP size has an effect on auditor switching. Keywords: management change, audit opinion, KAP size, auditor switching